2016
DOI: 10.3390/su8040396
|View full text |Cite
|
Sign up to set email alerts
|

What’s the Score? Walkable Environments and Subsidized Households

Abstract: Neighborhood walkability can influence individual health, social interactions, and environmental quality, but the relationships between subsidized households and their walkable environment have not been sufficiently examined in previous empirical studies. Focusing on two types of subsidized housing developments (Low-Income Housing Tax Credit (LIHTC) and Public Housing (PH)) in Austin, Texas, this study evaluates the neighborhood walkability of place-based subsidized households, utilizing objectively measured W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Many studies have shown that a good pedestrian-friendly environment can bring several benefits such as strengthening social interaction or cohesiveness, improving individual health and environmental health, as well as economic development [22,23]. Built environment characteristics play a vital role in affecting pedestrian-oriented environment and improving walkability, and the configuration of urban areas can influence pedestrians' walking trips [24,25].…”
Section: Characteristics Affecting Walkability and Measuring Walkabilitymentioning
confidence: 99%
“…Many studies have shown that a good pedestrian-friendly environment can bring several benefits such as strengthening social interaction or cohesiveness, improving individual health and environmental health, as well as economic development [22,23]. Built environment characteristics play a vital role in affecting pedestrian-oriented environment and improving walkability, and the configuration of urban areas can influence pedestrians' walking trips [24,25].…”
Section: Characteristics Affecting Walkability and Measuring Walkabilitymentioning
confidence: 99%
“…Measuring active travel support is challenging when “ways to measure active accessibility are as varied as the number of scholars that measure them” ( 19 ), and when urban form is entangled with socioeconomic patterns such that walkability and walking vary across environments (e.g., urban/rural, heavy/light traffic) and demographic measures such as income or race ( 20 25 ).…”
Section: Walkability and Walking: Environment And Behaviormentioning
confidence: 99%